Chlorophyll–total phosphorus relationships emerge from multiscale interactions from algae to catchments. Issue 6 (7th September 2022) - Olson, Carly R.; Jones, Stuart E.
Abstract: Chlorophyll and total phosphorus (TP) concentrations are key indicators of lake water quality and the relationship between them is a common tool for assessing lake trophic status. Despite the application of the chlorophyll–TP relationship in management settings, there is still an absence of a mechanistic understanding underlying its shape. We leveraged a process‐based model that focuses primarily on biogeochemical and physiological mechanisms to develop a framework that reconciles interactions between multiscale drivers of the chlorophyll–TP relationship, such as hydrologic P loads, lake shape, and algal physiology. We found that combinations of lake shape and hydrologic P load induce broad shifts in algal limitation status that underly the shape of the chlorophyll–TP relationship. Furthermore, we highlight the importance of algal traits in controlling shifts in limitation. Our framework ties key landscape and ecosystem features to biological limitation and provides a synthetic and process‐based understanding of the chlorophyll–TP relationship.